An IBE-based design for assured deletion in cloud storage. Issue 3 (4th May 2019) - Bentajer, Ahmed; Hedabou, Mustapha; Abouelmehdi, Karim; Igarramen, Zakaria; El Fezazi, Said
Abstract: Assured deletion of outsourced data in cloud storage is one of the most important issues in cloud storage. The use of encryption is a promising approach to address this issue. In this paper, we propose a design to achieve assured deletion in cloud storage built upon identity based cryptography (IBE). Compared with other designs known in the literature, foremost among them being FADE, the proposed design comes with a lightweight key management infrastructure. Furthermore, it offers other key management benefits inherent in identity-based cryptography such as key delegation and revocation. To demonstrate the practicality of the proposed design, we implement a fully featured prototype and evaluate its performance. Results analysis shows that the overhead time cost of the proposed design does not exceed 3 percent of the plaintext design. This rate decreases significantly for files with larger sizes, which makes it a relevant choice for use in real applications.